2017
DOI: 10.17072/1994-3598-2017-2-74-82
|View full text |Cite
|
Sign up to set email alerts
|

Soret-induced convection of binary and ternary mixtures in square cavity heating from above

Abstract: 74 ВЕСТНИК ПЕРМСКОГО УНИВЕРСИТ ЕТА ---------------------------------------------------------------- 2017• В настоящей работе исследована термоконцентрационная конвекция бинарных и трехком-понентных смесей с отрицательными отношениями разделения в квадратной полости при нагреве сверху в поле тяжести. Параметры бинарных смесей совпадают с параметрами трехкомпонентной смеси в предельном случае равенства нулю отношения разделения одной из компонент, что позволяет проследить влияние добавления еще одной примеси к б… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In [30][31][32], the emergence of thermogravitational convection in a ternary mixture, in flat cavities of various configurations heated from above, was numerically studied. The problem was solved using the equations of convection in multicomponent mixtures and neglecting the effects of cross diffusion.…”
Section: Thermal Diffusion and Convective Stability In Nonisothermal ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In [30][31][32], the emergence of thermogravitational convection in a ternary mixture, in flat cavities of various configurations heated from above, was numerically studied. The problem was solved using the equations of convection in multicomponent mixtures and neglecting the effects of cross diffusion.…”
Section: Thermal Diffusion and Convective Stability In Nonisothermal ...mentioning
confidence: 99%
“…The formation of the flow and distributions of impurity concentrations in a three-component mixture qualitatively repeats their formation in the case of a binary mixture. In [33], studies [30][31][32] were continued on the basis of a nonlinear stability analysis in the region of parameters dominated by monotonic long-wavelength instability. It was shown that for parameters significantly exceeding the critical ones, multivortex quasi-stationary flows are realized in the system.…”
Section: Thermal Diffusion and Convective Stability In Nonisothermal ...mentioning
confidence: 99%